Plan de seguridad en el trabajo para prevenir los riesgos laborales en la compañía “BOGAPACKAGING SYSTEMS CIA LTDA” en la parroquia Los Encuentros - Maza Chumapi, Jhoana Banesa (2024)
Safety at work is a factor that is an important part of the competencies of the companies, since thanks to the fact that they protect the safety of their workers not only for the fact of complying with the law, it contributes to the improvement of productivity, job satisfaction and above all the prevention of occupational hazards, this Curricular Integration Work was carried out with the purpose of proposing a safety plan at work to prevent occupational hazards in the company “BOGAPACKAGING SYSTEMS CIA LTDA” in the parish Los Encuentros, for the development was used simple descriptive research, through which variables of study were established which are: safety signs, protective equipment, place and work surface, machines and tools, transportation and storage, ergonomics and current regulations, to acquire bibliographic information that served as a basis for the development of the work; also used the non-experimental research with qualitative approach same that helped to study the variables in their natural state and then analyze them. The situational analysis was carried out with the results of the information techniques applied where it was obtained that the company complies with 95.18% of the inspection of compliance with legal regulations on safety and health at work, also provides training, provides personnel with the necessary protective equipment, the machinery is handled by authorized personnel and is subjected to periodic maintenance, there are signs that must be replaced since they are no longer in optimal conditions for proper operation. There is no good organization when storing and distributing materials and tools in the operating area; the vehicle parking areas do not provide guidance to help identify the space where vehicles can be parked; the restrooms are in perfect condition; however, they must be supplied with the necessary cleaning products on an ongoing basis; and training should emphasize compliance with regulations and providing a safe workspace. With the information gathered, a safety plan was drawn up to prevent occupational hazards in the company, with a reference budget of $23,240.50 dollars.